Grammatical Error Analysis on the First Grade of Olympiad Student’s Descriptive Text at SMP Islam 02 Pujon - Atika Kurniafita; Suhartatik Suhartatik (Verba: Journal of Applied Linguistics, 2022)
This research aims are: 1. To identify, classify and describe the type of grammatical error on the first grade of Olympiad student’s descriptive text at SMP ISLAM 02 Pujon based on Surface Strategy Taxonomy Theory by Dulay, 2. To find the causes of error made by the students in writing descriptive text using H.Douglas Brown’s Theory of possible source of error. The research was conducted by using descriptive qualitative method. The researcher used the instruction as the instrument to guide the student to write descriptive text, and the student’s descriptive text is considered as the data source. Based on research findings, the researcher found all error types and all source types with omission as the most type of error found, while intralingual is the most factor causing the student’s error on writing descriptive text.